PENERAPAN SISTEM PEMBUKTIAN TERBALIK DALAM TINDAK PIDANA PENCUCIAN UANG - Severius Hulu; Diantota Simanjuntak; Josua O.I Limbong; M.J.P Sagala (Jurnal Darma Agung, 2019)
One of the Government's efforts in emphasizing the rampant money laundering criminal acts or money laundring is giving special attention in the aspect of proof. Proof of true or whether the accused did the Act of charged, became the most important part of the law of criminal procedure. In the perspective of the science of criminal, law is known for three (3) theories about the law of proof: the burden of proof on the prosecution, the burden of proof on the defendant, the burden of proof that was balanced. The relationship of the system of reverse proof is limited on human rights (human rights) not inverted evidentiary assas regardless of the history of the establishment of this principle in the prevention and eradication of the crime of money laundering which in fact this principle is applied also in the prevention and eradication of criminal acts of corruption